2012
DOI: 10.1111/j.1743-6109.2011.02445.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Major Depression on Sexual Function in Women

Abstract: Introduction Eleven hundred eighty-four depressed women were entered into five short-term (8 weeks) studies of gepirone-extended release (ER) vs. placebo for treatment of major depressive disorder (MDD) (134001, 134002, and 134017), or atypical depressive disorder (ADD) (134004 and 134006). The effect of depression on sexual function was examined prior to treatment. Aim To determine the effect of depression on the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 19 publications
6
43
1
7
Order By: Relevance
“…No entanto, é relatado por vários autores 28,29 que a relação sexual não interfere no curso da gravidez. A associação inversa entre os resultados do BDI 11 e do FSFI 12 também já foi descrita anteriormente 25,28,30 . A depressão é um fator de risco para a disfunção sexual -causa desinteresse, apatia e sensação de fadiga, e potencializa outros sintomas que acabam por comprometer o desejo sexual -e, por outro lado, o desempenho sexual insatisfatório pode levar à depressão e causar conflitos relacionais, ou seja, desencadeia um círculo cumulativo entre disfunção sexual e depressão, no qual uma pode ser causa ou consequência da outra.…”
Section: Discussionunclassified
“…No entanto, é relatado por vários autores 28,29 que a relação sexual não interfere no curso da gravidez. A associação inversa entre os resultados do BDI 11 e do FSFI 12 também já foi descrita anteriormente 25,28,30 . A depressão é um fator de risco para a disfunção sexual -causa desinteresse, apatia e sensação de fadiga, e potencializa outros sintomas que acabam por comprometer o desejo sexual -e, por outro lado, o desempenho sexual insatisfatório pode levar à depressão e causar conflitos relacionais, ou seja, desencadeia um círculo cumulativo entre disfunção sexual e depressão, no qual uma pode ser causa ou consequência da outra.…”
Section: Discussionunclassified
“…In contrast to the two females described here, it has been found that women who suffer from depression have a greater sexual dysfunction compared to that of nondepressed females in the population and the degree of dysfunction has a relationship to the severity of mood disorder (8). In a prospective study, higher levels of anhedonia in females were found to be associated with reduced sexual desire on the subsequent day (9).…”
Section: Discussionmentioning
confidence: 69%
“…However, no significant association was observed between sexual dysfunction and other dimensions of general health (social function and depression). Fabre et al (2012) also investigated mental health and proposed that sexual and mental disorders resulted from low mental health levels in a large number of women (Fabre & Smith, 2012). Moreover, Montesi et al (2013) examined the effects of anger and anxiety on men's and women's sexual desire and came to the conclusion that increased anger level led to decreased sexual desire in both men and women.…”
Section: Discussionmentioning
confidence: 99%